Adjuvant ArtinM favored the host immunity against Cryptococcus gattii infection in C57BL/6 mice - Martins Oliveira-Brito, Patrícia Kellen; de Campos, Gabriela Yamazaki; Guimarães, Júlia Garcia; Machado, Michele Procópio; Serafim, Letícia Costa; Lazo Chica, Javier Emílio; Roque-Barreira, Maria Cristina; da Silva, Thiago Aparecido [UNESP] (Taylor & Francis, 2024)
Aim:Cryptococcus gattii causes a severe fungal infection with high mortality rate among immunosuppressed and immunocompetent individuals. Due to limitation of current antifungal treatment, new immunotherapeutic approaches are explored. Methods: This study investigated an immunization strategy utilizing heat-inactivated C. gattii with ArtinM as an adjuvant. C57BL/6 mice were intranasally immunized with heat-killed C. gattii and ArtinM was administrated either before immunization or along with HK-C. gattii. Mice were infected with C. gattii and the efficacy of the immunization protocol was evaluated. Results: Mice that received ArtinM exhibited increased levels of IL-10 and relative expression of IL-23 in the lungs, reduced fungal burden and preserved tissue integrity post-infection. Conclusion: Adjuvant ArtinM improved immunization against C. gattii infection in C57BL/6 mice.
Keywords: ArtinM; CD14; Cryptococcus gattii; immunomodulation; lectin; TLR2; vaccine